Analyzing an After-Sales Service Process Using Object-Centric Process Mining: A Case Study - Park, Gyunam; Aydin, Sevde; Ugur, Cuneyt; van der Aalst, Wil M. P. (Springer International Publishing Ag, 2024)
Process mining, a technique turning event data into business process insights, has traditionally operated on the assumption that each event corresponds to a singular case or object. However, many real-world processes are intertwined with multiple objects, making them object-centric. This paper focuses on the emerging domain of object-centric process mining, highlighting its potential yet underexplored benefits in actual operational scenarios. Through an in-depth case study of Borusan Cat's after-sales service process, this study emphasizes the capability of object-centric process mining to capture entangled business process details. Utilizing an event log of approximately 65,000 events, our analysis underscores the importance of embracing this paradigm for richer business insights and enhanced operational improvements.
5th International Conference on Process Mining (ICPM) -- OCT 23-27, 2023 -- Rome, ITALY
Keywords: Object-Centric Process Mining; Case Study; After-Sales Service Process